Temperature as a Universal Resetting Cue for Mammalian Circadian Oscillators - Buhr, Ethan D; Yoo, Seung-Hee; Takahashi, Joseph S (Science (American Association for the Advancement of Science), 2010)
Environmental temperature cycles are a universal entraining cue for all circadian systems at the organismal level with the exception of homeothermic vertebrates. We report here that resistance to temperature entrainment is a property of the suprachiasmatic nucleus (SCN) network and is not a cell-autonomous property of mammalian clocks. This differential sensitivity to temperature allows the SCN to drive circadian rhythms in body temperature, which can then act as a universal cue for the entrainment of cell-autonomous oscillators throughout the body. Pharmacological experiments show that network interactions in the SCN are required for temperature resistance and that the heat shock pathway is integral to temperature resetting and temperature compensation in mammalian cells. These results suggest that the evolutionarily ancient temperature resetting response can be used in homeothermic animals to enhance internal circadian synchronization.